Beachtlicher Erfolg der Hartz-III-Reform - Andrey Launov; Klaus Wälde (Wirtschaftsdienst, 2016)
Die Hartz-Reformen stellten zweifelsohne eine bedeutende Wende in der Entwicklung des Arbeitsmarktes dar. Obwohl die Reformen aus vier Teilen bestanden, war es hauptsächlich die Hartz-IV-Reform, die zu intensiven politischen und öffentlichen Debatten führte. Andrey Launov und Klaus Wälde zeigen, dass die Reform der Bundesanstalt für Arbeit (Hartz III), die ein Jahr vor der Hartz-IV-Reform implementiert wurde, einen viel größeren Beitrag zur Verringerung der Arbeitslosigkeit leistete. – – The Hartz reforms of the labour market constitute an important turning point in the evolution of the labour market in Germany. While the reforms consisted of four parts, it was especially the reform of the unemployment benefit system - the Hartz IV reform - that led to a strong response in the public and the media. Andrey Launov and Klaus Wälde demonstrate that the Hartz III reform of the German public employment agency (the "Bundesagentur für Arbeit (BA)"), that took place one year earlier, was much more successful in reducing unemployment. The reorganisation or the BA accounts for around 20% of the reduction of unemployment between 2005 and 2008. By contrast, the Hartz IV reform can account for only 5% of this reduction.
Keywords: E24; J65; J68; 330; Arbeitsmarktreform; Arbeitsverwaltung; Beschäftigungseffekt; Neue klassische Makroökonomik; Deutschland